2011
DOI: 10.1007/978-3-7091-0923-6_6
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Fractional Anisotropy and Apparent Diffusion Coefficient in Patients with Idiopathic Normal Pressure Hydrocephalus

Abstract: Since ventricular dilation and periventricular abnormal intensities are commonly seen in patients with idiopathic normal pressure hydrocephalus (INPH) on magnetic resonance imaging (MRI), dysfunction of white matter may have an important role in the mechanism causing symptoms of INPH. To clarify the pathophysiology of INPH, we analyzed axonal water dynamics using diffusion tensor MRI. Thirty-six patients with possible INPH were included. Regional fractional anisotropy (FA) and apparent diffusion coefficient (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 10 publications
2
20
0
Order By: Relevance
“…9,22,27,34,43,46 Some of these studies have reported that CSF drainage significantly increases FA in the periventricular WM and the CC and also significantly decreases ADC in these areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,22,27,34,43,46 Some of these studies have reported that CSF drainage significantly increases FA in the periventricular WM and the CC and also significantly decreases ADC in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…9 The patients were separated into 2 groups: those who had significant neurological improvement after the CSF tap test (17 patients) and those who had no improvement (19 patients). A statistically significant decrease (p < 0.05) in ADCs was detected only for the patients with neurological improvement.…”
Section: Dti Characteristics In Inph Patients Undergoing Csf Drainagementioning
confidence: 99%
See 1 more Smart Citation
“…This selective restriction of water molecule movement allows physical changes in periventricular white matter caused by hydrocephalus to be explored by diffusion anisotropy. Many DTI studies have reported the effect of hydrocephalus on periventricular white matter in patients with normal pressure hydrocephalus and in patients with hydrocephalus caused by a congenital anomaly [8][9][10][11][12][13][14][15][16][17]. However, little is known about hydrocephalus following stroke [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion-weighted MRI, by using magnetic field gradients to spatially label water molecules, reflects changes in water diffusion in tissues and is therefore considered sensitive to changes in the cerebral microstructure (11). Diffusion tensor imaging (DTI) measurements are sensitive to both absolute water diffusion and the direction of diffusion; for example, movement of water in normal pressure hydrocephalus from the white matter extracellular space to the intraventricular space is associated with a decrease in the apparent diffusion coefficient (ADC) (12). The fractional anisotropy (FA) changes in a wide variety of neurological disease states have been described (9,10).…”
mentioning
confidence: 99%